QUASI STATIC MECHANICAL PROPERTIES OF COCONUT SHELL OF DEHUSKED MATURE NUTS - E. E. Sudaria; D. C. Suministrado (International Coconut Community Journal, 1994)
The experiment was conducted to determine the (1) cracking, shearing, bending and tensile stresses of coconut shell at different positions of dehusked mature nut; (2) hardness of the coconut shell at different positions of dehusked mature nut; and (3) cracking streBB Of the dehusked mature coconut at different positions. The range values of the parameters under study were as follows: cracking stress of the coconut shell, 3,345, 083.2‑5, 397, 828.3 kg/m2; shearing stress of coconut shell, 574,984.9‑1, 258,830.9 kg/m2; bending stress of the coconut shell, 1,775,213.1‑ 23,463,299.9 kg/m2 , tensile stress of the coconut shell, 61,801.9‑259,003.3 kg/m2, hardness of the coconut shell, 150C51.5-150C57.6; and the cracking stress of the dehusked mature nut, 280,104.0‑440,277.7 kg/m2. The combined average stresses on bending, shearing, tensile, cracking of coconut shell, and cracking of dehusked mature nut revealed no significant difference on stresses at any positions of the dehusked mature nut. This suggests that nuts could be splitted at any position without significant difference on power expenditure. For the design of the splitter machine, cracking stress of the coconut shell should be viewed very well since this parameter had the highest stress.